2016
DOI: 10.1007/s10854-016-5234-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of low cost willemite based glass–ceramic for opto-electronic applications

Abstract: This paper presents a comprehensive study on thermal, structural and optical properties of novel willemite glass-ceramics. The precursor glass in the ZnO-SLS glass system was successfully prepared using conventional meltquenching technique and willemite (Zn 2 SiO 4 ) glass-ceramics were derived from this precursor glass by a control crystallization process. The effect of heat-treatment temperature on the phase transformation, morphology and size of Zn 2 SiO 4 crystal phase was examined using X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…It is fascinating to note that SiO 2 shows an amorphous characteristics at calcination temperature less than 700 °C [ 41 ]. According to Zaid et al [ 23 ], the crystallization formation of SiO 2 phase in ZnO–SiO 2 system could not be achieved at a temperature below 700 °C due to its amorphous state, and this conforms with the findings of Omar et al [ 28 ]. In a similar context, Babu et al [ 48 ] reported that at greater calcination temperatures beyond 700 °C, the ZnO atoms are the main diffusing component in ZnO/SiO 2 composite.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It is fascinating to note that SiO 2 shows an amorphous characteristics at calcination temperature less than 700 °C [ 41 ]. According to Zaid et al [ 23 ], the crystallization formation of SiO 2 phase in ZnO–SiO 2 system could not be achieved at a temperature below 700 °C due to its amorphous state, and this conforms with the findings of Omar et al [ 28 ]. In a similar context, Babu et al [ 48 ] reported that at greater calcination temperatures beyond 700 °C, the ZnO atoms are the main diffusing component in ZnO/SiO 2 composite.…”
Section: Resultssupporting
confidence: 85%
“…Willemite has several prospective applications such as photonic devices [ 17 , 18 ], adsorbents [ 19 , 20 ], and laser crystal systems [ 21 , 22 ]. Willemite is also serving as a host material for guest ions like transitional metals or rare earth metals due to its ability to display a wide range of multicolors for luminescence devices [ 11 , 23 , 24 , 25 , 26 , 27 , 28 ]. For instance, the luminescence properties of rare earth ions (RE 3+ ) such as the longer emission lifetime, sharper luminescence array, and the characteristic spectral features (owed to their filled 4f shells and spared by the exterior 5s 2 and 5p 6 orbitals) are some of the exciting factors for choosing them in modern day optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc silicate (Zn 2 SiO 4 ) or willemite is well known among researchers as a supreme and most suitable host matrix for glass phosphor and other optoelectronic materials, since it has a quite huge band gap around 5.5 eV, high chemical compound stability, and a great glass transparency [7]. Besides, it also has another special feature-a large excitation binding energy-allowing it to be used as an enhancer for triggering the luminescence inside the neon discharged lamps, fluorescent lamps, black-and-white televisions, colour televisions, oscilloscopes, laser technology, optical communications, optical fibre amplifiers, waveguides, and light emitting diodes (LED) [8][9][10]. Nowadays, the production of low-cost zinc silicate glass and glass-ceramics is a topic of interest among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…This is including the conventional sol–gel technique [16,17,18] and solid state method [19,20,21,22]. In addition, other researchers reported the production of willemite by hydrothermal method [23,24], co–precipitation method [25], sonochemical method [26], spray drying method [27], spray pyrolysis method [28,29], super critical water methods [30,31] and solvothermal method [32].…”
Section: Introductionmentioning
confidence: 99%